Biosensor Selection of Small Compounds, Modulating a Complex Formation between Cytochrome P450s and NADPH-Dependent P450 Oxidoreductase - Ershov, P.V.; Yablokov, E.O.; Mezentsev, Y.V.; Kaluzhskiy, L.A.; Luschik, A.Ya.; Tumilovich, A.M.; Karputs, A.Yu.; Gilep, A.A.; Ivanov, А.S. (Biomedical Chemistry: Research and Methods, 2020)
The study of the effect of low-molecular-weight compounds (substrates, endogenous metabolites, drugs and xenobiotics) on the kinetic and equilibrium parameters of functionally significant binary protein-protein interactions (PPIs) is of both fundamental and clinical importance. The surface plasmon resonance (SPR) is the method of the first choice for studying PPIs. Earlier, SPR analysis revealed the modulating effect of steroidal substrates on the affinity of interactions between steroidogenic microsomal cytochromes P450 (CYP) and their redox partner (cytochrome b5). In this work, we have shown the suitability of the experimental approach for assessing the selective effect of the cofactor NADPH on the interaction between cytochromes CYP3A4 or CYP2E1 with NADPH-dependent P450 oxidoreductase (CPR). Experiments have shown that the CYP3A4/CPR complex is not modulated by NADPH, while the dissociation rate of the CYP2E1/CPR complex in the presence of NADPH significantly decreased: the koff values in the absence and presence of NADPH were (3.6 ± 0.2) • 10-3 s-1 and (3.8 ± 0.2) • 10-4 s-1, respectively. Thus, in the presence of NADPH, an increase in the affinity of CYP2E1/CPR complex formation by approximately one order of magnitude was observed, while NADPH did not affect the kon value of this complex. Co-injection of NADPH at the CYP2E1/CPR complex preformed in the absence of NADPH had minor influence on the koff values (<10%). This suggests a stabilizing role of NADPH for the CYP2E1/CPR complex formation. Thus, the use of our approach made it possible to assess the effect of the main electron supplier for the microsomal cytochrome P450 monooxygenase system on the kinetic rate constants of CYP/CPR complexes.